2020
DOI: 10.3390/antiox9121259
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Specialized Pro-Resolving Lipids Mediators on Cardiac Fibrosis via NRF2 Activation

Abstract: Heart disease is the number one mortality disease in the world. In particular, cardiac fibrosis is considered as a major factor causing myocardial infarction and heart failure. In particular, oxidative stress is a major cause of heart fibrosis. In order to control such oxidative stress, the importance of nuclear factor erythropoietin 2 related factor 2 (NRF2) has recently been highlighted. In this review, we will discuss the activation of NRF2 by docosahexanoic acid (DHA), eicosapentaenoic acid (EPA), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 206 publications
(247 reference statements)
0
18
0
Order By: Relevance
“…Once in the brain, DHA is esterified into membrane phospholipids, being released and converted to bioactive mediators during neurotransmission and following brain injury [ 77 ]. The antioxidant properties of DHA and its metabolites, resolvins, neuroprotectins and 4-hydroxy-2E-hexenal, are mediated by Nrf2 activation and involve upregulation of heme oxygenase 1 (HO-1) to protect the brain against ischemic damage [ [78] , [79] , [80] ]. Post-stroke administration of DHA is effective in reducing brain injury [ [81] , [82] , [83] ] and improving sensorimotor function [ 84 , 85 ].…”
Section: Protective Role Of Scfas Against Oxidative and Mitochondrial Stress Involving Keap1-nrf2 Signalingmentioning
confidence: 99%
“…Once in the brain, DHA is esterified into membrane phospholipids, being released and converted to bioactive mediators during neurotransmission and following brain injury [ 77 ]. The antioxidant properties of DHA and its metabolites, resolvins, neuroprotectins and 4-hydroxy-2E-hexenal, are mediated by Nrf2 activation and involve upregulation of heme oxygenase 1 (HO-1) to protect the brain against ischemic damage [ [78] , [79] , [80] ]. Post-stroke administration of DHA is effective in reducing brain injury [ [81] , [82] , [83] ] and improving sensorimotor function [ 84 , 85 ].…”
Section: Protective Role Of Scfas Against Oxidative and Mitochondrial Stress Involving Keap1-nrf2 Signalingmentioning
confidence: 99%
“…The nuclear factor erythropoietin 2 related factor 2 (NRF2) is involved in the process of controlling oxidative stress; due to its antioxidant activity, the NRF2 could protect the heart from the onset of cardiac fibrosis. Therefore, it is interesting that EPA, DHA, and some specialized pro-resolving lipid mediators (SPMs), such as resolvin D1 (RvD1), are capable of activating NRF2, demonstrating efficacy against cardiac fibrosis and therefore demonstrating effectiveness against HF and MI onset [ 73 ]. Furthermore, some mechanistic studies propose a different cardioprotective mechanism of n-3 PUFAs that involves their interaction with the free fatty acid receptor 4 (Ffar4), a G-protein coupled receptor (GPR) for long-chain fatty acids.…”
Section: Heart Failure and Pufasmentioning
confidence: 99%
“…Therefore, we isolated and cultured the CFs from the neonatal mice hearts and explored the possible mechanism of FGF21 on inhibiting cardiac fibrosis. Oxidative stress is one of the causes of cardiac fibrosis in the injured heart [35]; we treated the CFs with H 2 O 2 to mimic the ischemic myocardium and detected the effect of FGF21 on the activation of TGF-β1-Smad2/3 signaling in the CFs. Western blotting results showed that compared with control, H 2 O 2 significantly increased the protein expression levels of TGF-β1, Smad2/3, MMP2 and MMP9 of CFs (all p < 0.01), which were inhibited by rhFGF21 intervention (all p < 0.01).…”
Section: Exercise Training Up-regulated Fgf21 Expression and Alleviated Cardiac Dysfunction And Cardiac Fibrosis In The Infarcted Heartmentioning
confidence: 99%